2022
DOI: 10.3390/jpm12101690
|View full text |Cite
|
Sign up to set email alerts
|

Dental Implant and Natural Tooth Micro-Movements during Mastication—In Vivo Study with 3D VIC Method

Abstract: In the paper, using the video image correlation method, a study of the micro-movement pattern of the dental implant and of a normal was performed. It is revealed that there are great differences between these two situations. The linear displacement type of the dental implant refers to the linear elastic modulus of bone tissue in the case of normal bite forces. It seems that the major influencing factor regarding the type and value of implant micro-movement is defined by the underlying bone tissue. It is to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Original studies [17] using the video image correlation method were conducted to determine the micromovements of the dental implant and the bone base, and they show that there are significant differences between these two objects. The linear type of displacement of a dental implant refers to the linear modulus of elasticity of bone tissue under regular occlusion forces.…”
Section: Discussionmentioning
confidence: 99%
“…Original studies [17] using the video image correlation method were conducted to determine the micromovements of the dental implant and the bone base, and they show that there are significant differences between these two objects. The linear type of displacement of a dental implant refers to the linear modulus of elasticity of bone tissue under regular occlusion forces.…”
Section: Discussionmentioning
confidence: 99%
“…From a functional point of view, the calculated value is very small, being below the acceptable ones, presented in the specialized literature. [ 8 ] Figure 6B shows the state of shear stresses in the XY plane. Calculated stress value is SXY = 0.32 E7 N m −2 , much lower than Young modulus that means an elastic behavior, without dangerous problems for the composite structure.…”
Section: Finite Element Modeling (Fem) Of the Biocomposite Structurementioning
confidence: 99%
“…This is thought to be chiefly because FISPs do not have a periodontal ligament and are prone to occlusal overloading of the opposing teeth (Park et al., 2021). Moreover, a study reported clear differences in the micro‐movement patterns between FISPs and natural teeth (Száva et al., 2022). Thus, the difference in the load‐bearing capacity of the two prostheses indicate a different distribution of mechanical forces, which may affect the residual teeth including the adjacent teeth.…”
Section: Introductionmentioning
confidence: 99%